Pupil size variations correlate with physical effort perception - Zénon, Alexandre; Sidibé, Mariam; Olivier, Etienne (Frontiers in Behavioral Neuroscience, 2014)
It has long been established that the pupil diameter increases during mental activities in proportion to the difficulty of the task at hand. However, it is still unclear whether this relationship between the pupil size and effort applies also to physical effort. In order to address this issue, we asked healthy volunteers to perform a power grip task, at varied intensity, while evaluating their effort both implicitly and explicitly, and while concurrently monitoring their pupil size. Each trial started with a contraction of imposed intensity, under the control of a continuous visual feedback. Upon completion of the contraction, participants had to choose whether to replicate, without feedback, the first contraction for a variable monetary reward, or whether to skip this step and go directly to the next trial. The rate of acceptance of effort replication and the amount of force exerted during the replication were used as implicit measures of the perception of the effort exerted during the first contraction. In addition, the participants were asked to rate on an analog scale, their explicit perception of the effort for each intensity condition. We found that pupil diameter increased during physical effort and that the magnitude of this response reflected not only the actual intensity of the contraction but also the subjects’ perception of the effort. This finding indicates that the pupil size signals the level of effort invested in a task, irrespective of whether it is physical or mental. It also helps refining the potential brain circuits involved since the results of the current study imply a convergence of mental and physical effort information at some level along this pathway.